Cover Picture: Visible Light‐Promoted Three‐Component Carboazidation of Unactivated Alkenes with TMSN3 and Acrylonitrile (Chin. J. Chem. 11/2018). Issue 11 (15th October 2018) - Yang, Bo; Ren, Xiang; Shen, Xuzhong; Li, Tongtong; Lu, Zhan
Abstract : The cover picture shows a visible light promoted three‐component carboazidation of unactivated alkenes with TMSN3 and acrylonitrile. The photoredox reactions proceed through the azide radical generation, radical addition to alkenes in tandem with radical Michael addition to acrylonitrile. This protocol is operationally simple for straightforward access to azido derivatives with good functional group tolerance without any stoichiometric oxidants. More details are discussed in the article by Lu et al. on page 1017–1023. Abstract : The cover picture shows a visible light promoted three‐component carboazidation of unactivated alkenes with TMSN3 and acrylonitrile. The photoredox reactions proceed through the azide radical generation, radical addition to alkenes in tandem with radical Michael addition to acrylonitrile. This protocol is operationally simple for straightforward access to azido derivatives with good functional group tolerance without any stoichiometric oxidants. More details are discussed in the article by Lu et al. on page 1017–1023.